The Concept of Civilized Humans in Islamic Education: A Study of the Thought of Syed Muhammad Naquib al-Attas - Ahmad Abdullah Faqih; Muhammad Arif Syihabuddin (Penerbit Hellow Pustaka, 2026)
This study aims to explore and analyze the concept of civilized human beings (insan adabi) in the Islamic educational thought of Syed Muhammad Naquib al-Attas as a philosophical-pedagogical foundation for formulating an alternative paradigm for contemporary Islamic education. The study uses a qualitative approach with a library research design, examining al-Attas's primary works such as Islam and Secularism (1993), The Concept of Education in Islam (1980), and Prolegomena to the Metaphysics of Islam (1995). Data were analyzed using a descriptive-analytical method through three stages: description of al-Attas's concept of human, analysis of epistemological-ontological-axiological foundations, and interpretation of contemporary relevance. The results of the study show that al-Attas' concept of human beings emphasizes the formation of an adabi human being who has a multi-dimensional existential structure (intellectual, spiritual, moral) that is developed integrally through the process of ta'dib instilling adab, developing reason, and forming morals. Adab is defined as the recognition and acknowledgment of the proper place for everything in the hierarchical order of being (maratib al-wujud). The study concludes that al-Attas' concept of human beings offers a holistic and integrative paradigm of Islamic education, capable of responding to the crisis of modern education (secularization, fragmentation, dehumanization) by producing a generation of Muslims who have strong faith, broad knowledge, and noble morals to answer contemporary challenges without losing their Islamic identity.